Implementasi Relaksasi Autogenik untuk Menurunkan Nyeri pada Pasien Pasca Operasi Sectio Caesarea - Areksah, Recy; Sukmaningtyas, Wilis; Haniyah, Siti (Yayasan Inspirasi El Burhani, 2025)
Introduction: Caesarean section, also known as sectio caesarea (SC), is a significant surgical procedure that often causes anxiety and pain, especially during the recovery period. This pain can stem from the incision wound, uterine contractions, and psychological factors such as stress and emotional tension. Objective: This study aimed to investigate the effectiveness of autogenic relaxation as a non-pharmacological method for reducing pain in patients after a caesarean section. Method This pre-experimental study applied a one-group pretest–posttest design conducted at Goeteng Taroenadibrata General Hospital, Purbalingga, involving 30 postoperative SC patients. Pain levels were assessed using the Numeric Rating Scale (NRS) before and after the implementation of autogenic relaxation. The intervention was performed in several structured steps: patients were educated on the importance of relaxation and provided with instructional leaflets, guided autogenic relaxation sessions were conducted for approximately 20 minutes in a calm environment, focusing on breathing and self-suggestion techniques to promote body awareness and relaxation, and pain intensity was reassessed five minutes after the intervention. Result: The research results showed a significant decrease in pain levels after patients practiced autogenic relaxation. Before the intervention, most patients experienced moderate to severe pain. However, after the therapy, 90% of patients reported mild pain, and no one experienced severe pain anymore. A significant decrease in pain levels was observed after autogenic relaxation was administered. Conclusion Autogenic relaxation proved effective in reducing postoperative pain among caesarean section patients. This technique can serve as a complementary non-pharmacological intervention in nursing practice to enhance patient comfort, promote relaxation, and support the overall recovery process.